2000
DOI: 10.1111/j.1469-7793.2000.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous excitatory drive to the respiratory system in rapid eye movement sleep in cats

Abstract: A putative endogenous excitatory drive to the respiratory system in rapid eye movement (REM) sleep may explain many characteristics of breathing in that state, e.g. its irregularity and variable ventilatory responses to chemical stimuli. This drive is hypothetical, and determinations of its existence and character are complicated by control of the respiratory system by the oscillator and its feedback mechanisms. In the present study, endogenous drive was studied during apnoea caused by mechanical hyperventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
1
38
0
2
Order By: Relevance
“…However, this concept was first identified in physiological experiments investigating the control of intercostal muscles. Hypocapnia produced by constant mechanical hyperventilation in anaesthetized (Sears et al 1982) or conscious (Horner et al 1994a,b;Orem et al 2000) animal preparations reveals a background tonic drive to the intercostal nerves and muscles independent of respiratory-related activity. Most relevant to this discussion, these studies showed for the first time that the tonic drive to respiratory muscle could be identified and studied independently of spontaneous respiratory rhythm in an intact conscious organism (Horner et al 1994a,b).…”
Section: Overview Of the Respiratory Systemmentioning
confidence: 99%
“…However, this concept was first identified in physiological experiments investigating the control of intercostal muscles. Hypocapnia produced by constant mechanical hyperventilation in anaesthetized (Sears et al 1982) or conscious (Horner et al 1994a,b;Orem et al 2000) animal preparations reveals a background tonic drive to the intercostal nerves and muscles independent of respiratory-related activity. Most relevant to this discussion, these studies showed for the first time that the tonic drive to respiratory muscle could be identified and studied independently of spontaneous respiratory rhythm in an intact conscious organism (Horner et al 1994a,b).…”
Section: Overview Of the Respiratory Systemmentioning
confidence: 99%
“…The database for this study was a subset from the databases used for our previously published studies [6,7,8,9,49,50,60]. The selection of the neurons and neuronal populations for this study was based on the duration of available spike trains (4000-65000 spikes).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures of surgical preparation of the animals were described previously [7,50,52]. Surgery was performed under isoflourane (cats, 2-5%), halothane (cats, 1-2%), or pentobarbital sodium (rabbits, 25-35 mg/kg) anesthesia using aseptic procedures.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations